Occupational Therapy Practice in Mental Health: Models, Conditions, Interventions, and Recovery - Machingura, Tawanda (Bentham Science Publishers, 2025)
Structured across four sections, the book begins with foundational models of practice, including MOHO, CMOP-E, PEO, and the Kawa model, before examining common and often underrepresented mental health conditions such as eating disorders and personality disorders. Building on this foundation, the book highlights occupational therapyspecific interventions, from psycho-education and CBT to sensory approaches and group work, offering practical tools and resources for clinicians. The final section critically discusses recovery, social determinants of mental health, participatory citizenship, and the role of technology in shaping future practice. Designed for flexible use, each chapter functions as a standalone resource, enabling readers to dip into specific topics as needed. Key Features Explains core occupational therapy models used in mental health practice. Addresses diverse conditions, including underrepresented diagnoses like eating and personality disorders. Demonstrates occupational therapyspecific interventions within interdisciplinary teams. Provides practice tools, instruments, and case-based examples for learners and professionals. Critiques recovery-oriented practice and explores emerging roles for technology and citizenship.